2018
DOI: 10.7759/cureus.3466
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Supporting Selective Dorsal Rhizotomy for Treatment of Spastic Cerebral Palsy

Abstract: The objective of this review is to analyze the evidence supporting selective dorsal rhizotomy (SDR) for the treatment of spastic cerebral palsy (CP). We reviewed 85 outcome studies from 12 countries between 1990 and 2017. The published results are overwhelmingly supportive of SDR, and 39 studies form a basis for this review. Also included is some of the clinical experience of the senior author.The results show that SDR plus postoperative physiotherapy (PT) improved gait, functional independence, and self-care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 40 publications
2
27
0
3
Order By: Relevance
“…EMG electromyography, SD standard deviation, mA milliampere, ms millisecond Table 3 Changes of muscle tone, muscle strength of the target muscles, and ROM of the joints involved (passive) pre-and postop favorable outcome. Similar results were reported from other centers when SDR was performed in the traditional manner [14][15][16][17]. Further investigation in our study revealed that cases when SDR performed to younger than 6 years old had much Fig.…”
Section: Discussionsupporting
confidence: 91%
“…EMG electromyography, SD standard deviation, mA milliampere, ms millisecond Table 3 Changes of muscle tone, muscle strength of the target muscles, and ROM of the joints involved (passive) pre-and postop favorable outcome. Similar results were reported from other centers when SDR was performed in the traditional manner [14][15][16][17]. Further investigation in our study revealed that cases when SDR performed to younger than 6 years old had much Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The beneficial effects of the operation extend into adulthood [1,2]. Amassed evidence in the literature and clinical experience with the procedure in the last four decades indicate the efficacy of SDR in the treatment of spastic diplegia [3]. By contrast, there was only a single publication on the outcome of SDR on children with spastic hemiplegia.…”
Section: Introductionmentioning
confidence: 99%
“…Las dimensiones de la calidad de vida en las que se han obtenido puntuaciones medias más bajas han sido: desarrollo personal, inclusión social y bienestar material. En un estudio llevado a cabo por Park et al, (19) también se encontraron medias inferiores en inclusión social pero en este caso la otra dimensión con una media inferior al resto fue la dimensión de relaciones interpersonales.…”
Section: Discussionunclassified